Penerapan Akuntansi Pertanggungjawaban sebagai Alat Penilaian Kinerja Pusat Biaya: : Studi Kasus Cafe Hasanah - Sambas, Yolanda; Mardiani, Sherlita; Ripaldo Hsb, Muhammad Rezki (Economic Reviews Journal, 2024)
The purpose of this study is to assess and investigate how accounting systems might improve management performance evaluation. The focus of this investigation is Hasanah Cafe. is a company involved in the trade of goods related to food and drink. Qualitative methods were employed in the inquiry. To characterize objects precisely as they are, researchers employ a descriptive analysis methodology. Budgets have been created using bottom-up budgeting, however neither responsibility center codes nor a distinction between controlled and uncontrollable expenditures have been made. Budgets have been created using bottom-up budgeting, however neither responsibility center codes nor a distinction between controlled and uncontrollable expenditures have been made. The discussion's findings demonstrate that when the budget is created using the accountability accounting approach, the responsibility center manager is only expected to be accountable for costs that can be managed. The aggregate difference between the predicted and realized costs shows that the commercial food and beverage business' performance evaluation was successfully completed. The results demonstrate that by creating a responsible accounting system, management may more readily evaluate performance from lowest to highest rating. Accountability accounting may be thought of as useful if budgets are used and met in accordance with predefined standards. The aggregate difference between the predicted and realized costs shows that the commercial food and beverage business' performance evaluation was successfully completed. The results demonstrate that by creating a responsible accounting system, management may more readily evaluate performance from lowest to highest rating. Accountability accounting may be thought of as useful if budgets are used and met in accordance with predefined standards. The aggregate difference between the predicted and realized costs shows that the commercial food and beverage business' performance evaluation was successfully completed. The results demonstrate that by creating a responsible accounting system, management may more readily evaluate performance from lowest to highest rating. Accountability accounting may be thought of as useful if budgets are used and met in accordance with predefined standards.